A VISIR Lab Server for the iLab Shared Architecture - Garbi Zutin, Danilo (International Journal of Online and Biomedical Engineering (iJOE), 2011)
This paper describes the work done at the Carinthia University of Applied Sciences towards integrating VISIR-based labs on the iLab architecture. The Virtual Systems in Reality (VISIR) project is carried out by the Blekinge Institute of Technology, Sweden and features a platform for performing experiments in different domains.